Ergebnisvergleich von multimorbiden gefäßchirurgischen Patienten mit und ohne Majoramputation in einer deutschen stationären geriatrischen Rehabilitationsklinik - Grund, Stefan; Kieser, Meinhard (Zeitschrift für Gerontologie und Geriatrie, 2018)
Background: In the course of demographic developments, an increase of vascular surgical procedures including major amputations in very elderly, multimorbid geriatric patients is expected. Due to the high vulnerability of these patients, geriatric rehabilitation directly following the acute inpatient treatment is likely to improve the abilities of these patients. This issue is not well analyzed in Germany up to now. Materials and methods: This retrospective study includes all patients who were admitted to our clinic for geriatric rehabilitation after vascular surgery between 01 June 2012 and 31 December 2013. Geriatric assessments at the time of admission and discharge were considered. The group was divided into rehabilitation patients with major limb amputation and nonmajor limb amputation. Both groups were analyzed with respect to functional parameters and activities in daily life (ADL) during the course of rehabilitation as well as the discharge location (home versus nursing home). Results: A total of 30 major-limb-amputee and 77 nonmajor-limb-amputee rehabilitants could be analyzed. Before surgical intervention, 100 % of patients lived in a home care situation. The median age was 78.3 years. During rehabilitation, both groups showed highly significant improvements in ADL (Barthel index), Timed Up and Go test, walking distance, and stair climbing; however the nonmajor amputees surpassed the major amputees in most mobility assessments especially in the five chair-rising test. The rehabilitation time (median) was 41.8 days for major and 23.9 days for nonmajor amputees. More than 90 % of the rehabilitants in both groups could be discharged home. Conclusion: The data from this retrospective study indicate that even advanced old age, multimorbid patients benefit from geriatric rehabilitation after vascular surgery intervention. Although less distinct than the group of minor amputee rehabilitants, highly significant improvements were also demonstrated in the group of major amputee rehabilitants as assessed in the discharge mobility and ADL results compared to the admission assessment results. These improvements were achieved in an adequate time period and led to discharge into home care for the majority of patients.
First Online: 23 January 2015
Gesehen am 21.05.2019